Information Model of the Process of Lifting Long Span Roof - Osipov, A.F.; Chernenko, K.V. (Science and Innovation, 2024)
Introduction. Development of information systems allows creating, modelling and improving technological solutions of lifting and assembling long span roofs. Problem Statement. Development of new organizational and technological solutions, technologies and methods requires a complex research at the initial stages of their creation with the help of software. These studies help to avoid problems and misleading that may occurs as a result of wrong decisions. Purpose. To substantiate organizational and technological decisions in the development of new technology of lifting long span roofs, by creating an information model of the process for lifting long span roofs with certain detalization to analyze the components of the process, conditions and disadvantages that occurs when using the new technology of lifting long span roofs. Materials and Methods. Research and development of information model of the process of lifting large-scale coverings with the help of newly created load-lifting walking modules. A method for simulating the process, conditions, and objects involved in lifting large-scale coatings was used. Results. In the process of modelling based on the proposed information model of the process, organizational and technological peculiarities of the use of new technology of lifting long span roofs with simultaneous arrangement of permanent supports and determined values of the experimental values were considered as a certain series-discrete order of visual images and parameters. Conclusions. Creating an information model of the process, which essentially belongs to the class of imitation models has allowed significantly reducing the time and substantiate the organizational and technological decisions while development of new technology. This has enabled not only comparing and identifying the conditions under which such technology has significant advantages over existing ones, but also improving it.